The B3 domain-containing transcription factor ZmABI19 coordinates expression of key factors required for maize seed development and grain filling. Issue 1 (23rd November 2020) - Yang, Tao; Guo, Liangxing; Ji, Chen; Wang, Haihai; Wang, Jiechen; Zheng, Xixi; Xiao, Qiao; Wu, Yongrui
Abstract: Grain filling in maize ( Zea mays ) is regulated by a group of spatiotemporally synchronized transcription factors (TFs), but the factors that coordinate their expression remain unknown. We used the promoter of the grain filling-specific TF gene Opaque2 ( O2 ) to screen upstream regulatory factors and identified a B3 domain TF, ZmABI19, that directly binds to the O2 promoter for transactivation. zmabi19 mutants displayed developmental defects in the endosperm and embryo, and mature kernels were opaque and reduced in size. The accumulation of zeins, starch and lipids dramatically decreased in zmabi19 mutants. RNA sequencing revealed an alteration of the nutrient reservoir activity and starch and sucrose metabolism in zmabi19 endosperms, and plant phytohormone signal transduction and lipid metabolism in zmabi19 embryos. Chromatin immunoprecipitation followed by sequencing coupled with differential expression analysis identified 106 high-confidence direct ZmABI19 targets. ZmABI19 directly regulates multiple key grain filling TFs including O2, Prolamine-box binding factor 1, ZmbZIP22, NAC130, and Opaque11 in the endosperm and Viviparous1 in the embryo. A number of phytohormone-related genes were also bound and regulated by ZmABI19. Our results demonstrate that ZmABI19 functions as a grain filling initiation regulator. ZmABI19 roles in coupling early endosperm and embryo development are also discussed. Abstract : ZmABI19 directly regulates the key factors that coordinate endosperm and embryo development and grain filling in maize.